2021
DOI: 10.5296/jei.v7i1.18267
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Learning Activities on Waste and Sewage Management Using Question and Problems-Based Learning for Undergraduate Students of Mahasarakham University, Thailand

Abstract: In this study, the purposes of this research were to study and compare knowledge about waste and sewage management, environmental ethics and environmental volunteers using question and problems-based learning, before and after class of undergraduate students, to compare knowledge about waste and sewage management, environmental ethics and the environmental volunteers of undergraduate students with different gender and Grade Point Average (GPA). The sample used in the research were 111 undergraduate students be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…and for the benefit of all things that depend on the environment to survive without losing the relationship between people and the environment. This is consistent with the findings of Praimee and Boonserm (2021) found that the undergraduate students of different gender were no different knowledge about waste and sewage management. And Thinkhamchoet, Wongchantra and Bunnaen (2021) found that the undergraduate students of different gender were no different of knowledge about environmental conservation.…”
Section: Discussionsupporting
confidence: 92%
“…and for the benefit of all things that depend on the environment to survive without losing the relationship between people and the environment. This is consistent with the findings of Praimee and Boonserm (2021) found that the undergraduate students of different gender were no different knowledge about waste and sewage management. And Thinkhamchoet, Wongchantra and Bunnaen (2021) found that the undergraduate students of different gender were no different of knowledge about environmental conservation.…”
Section: Discussionsupporting
confidence: 92%